Study of variability induced by random dopant fluctuation in Fe DS-SBTFET. (July 2022) - Ghosh, P.; Bhowmick, B.
Abstract: This paper explores the affectability of random dopant fluctuation (RDF) on the performance of Ferroelectric Dopant Segregated Schottky Barrier (Fe DS-SB) TFET by utilizing 3-D TCAD simulation. The simulation technique involves the device bifurcation into rectangular coordinates where the doping charges are placed randomly as individual and discrete dopants. Threshold voltage varies significantly due to variation in source-channel dopant concentration. The dependency of threshold voltage standard deviation on various source doping concentration has been studied. Doping variability within the channel and drain regions mainly leads to alteration in ON state current. Moreover, the impact of temperature (300 K–500 K) on switching characteristics of the proposed device has been investigated.